Expansion of CD45RA−FOXP3++ regulatory T cells is associated with immune tolerance in patients with combined kidney and bone marrow transplantation. Issue 8 (9th August 2021) - Kwon, Yeongbeen; Lee, Kyo Won; Kim, You Min; Park, Hyojun; Jung, Min Kyung; Choi, Young Joon; Son, Jin Kyung; Hong, JuHee; Park, Su‐Hyung; Kwon, Ghee Young; Yoo, Heejin; Kim, Kyunga; et al.
Abstract: Objectives: Simultaneous transplantation of a solid organ and bone marrow from the same donor is a possible means of achieving transplant tolerance. Here, we attempted to identify biomarkers that indicate transplant tolerance for discontinuation of immunosuppressants in combined kidney and bone marrow transplantation (CKBMT). Methods: Conventional kidney transplant (KT) recipients ( n = 20) and CKBMT recipients ( n = 6) were included in this study. We examined various immunological parameters by flow cytometry using peripheral blood mononuclear cells (PBMCs), including the frequency and phenotype of regulatory T (Treg) cell subpopulations. We also examined the suppressive activity of the Treg cell population in the setting of mixed lymphocyte reaction (MLR) with or without Treg cell depletion. Results: Among six CKBMT recipients, three successfully discontinued immunosuppressants (tolerant group) and three could not (non‐tolerant group). The CD45RA − FOXP3 ++ Treg cell subpopulation was expanded in CKBMT recipients compared to conventional kidney transplant patients, and this was more obvious in the tolerant group than the non‐tolerant group. In addition, high suppressive activity of the Treg cell population was observed in the tolerant group. The ratio of CD45RA − FOXP3 ++ Treg cells to CD45RA − FOXP3 + cells indicated good discrimination between the tolerant and non‐tolerant groups. Conclusion: Thus, our findings propose a biomarker that can distinguish CKBMT patients who achieve transplant tolerance and are eligible for discontinuation of immunosuppressants and may provide insight into tolerance mechanisms in CKBMT. Abstract : In this study, we attempted to identify biomarkers that indicate transplant tolerance for discontinuation of immunosuppressants in combined kidney and bone marrow transplantation (CKBMT). We focused on CD4 + CD25 + CD127 lo FoxP3 + regulatory T (Treg) cells and their subpopulations and found that the CD45RA – FoxP3 ++ Treg cell subpopulation was expanded in the tolerant group among CKBMT recipients. As a result, the ratio of CD45RA – FoxP3 ++ Treg cells to CD45RA – FoxP3 + cells indicated good discrimination between the tolerant and non‐tolerant groups. Our current findings propose a biomarker that can distinguish CKBMT patients who achieve transplant tolerance and are eligible for discontinuation of immunosuppressants and provide insight into tolerance mechanisms in CKBMT.